Potential Microplastic-Degrading Bacteria from Mangrove Sediment in The Paluh Getah Area, Percut Sei Tuan District - Ahmad Shafwan S. Pulungan; Larasati Arum Utami; Marlinda Nilan Sari Rangkuti; Ayu Putri Ningsih; Cindy Suci Muliandhira (Jurnal Penelitian Pendidikan IPA, 2025)
Microplastic pollution poses a severe threat to marine ecosystems due to its persistence and toxicity, necessitating innovative biodegradation strategies. This study explored the potential of bacteria isolated from mangrove sediments of the Paluh Getah mangrove forest, North Sumatra, to degrade common microplastics, including LDPE, HDPE, PET, PP, and PS. Ten bacterial isolates were obtained and screened for their ability to grow on microplastic-supplemented mineral salt medium over 20 days. Three isolates (BPM 5, BPM 9, and BPM 10) demonstrated robust growth, with biochemical tests confirming catalase activity critical for managing oxidative stress during plastic degradation. Molecular identification via 16S rRNA gene sequencing revealed the isolates as Enterobacter sp. and Brevibacillus parabrevis, both known for their biodegradation capacities. The findings underscore the diverse metabolic pathways these bacteria employ to utilize microplastics as carbon sources. This research highlights the promise of mangrove sediment bacteria as eco-friendly bioremediation agents to mitigate microplastic pollution in coastal environments. Further studies are required to optimize degradation conditions and elucidate enzymatic mechanisms to enhance practical applications.